Chemistry of Volatile Organic Compounds in the Los Angeles Basin: Formation of Oxygenated Compounds and Determination of Emission Ratios. Issue 4 (22nd February 2018) - de Gouw, J. A.; Gilman, J. B.; Kim, S.‐W.; Alvarez, S. L.; Dusanter, S.; Graus, M.; Griffith, S. M.; Isaacman‐VanWertz, G.; Kuster, W. C.; Lefer, B. L.; Lerner, B. M.; McDonald, B. C.; et al.
Abstract: We analyze an expanded data set of oxygenated volatile organic compounds (OVOCs) in air measured by several instruments at a surface site in Pasadena near Los Angeles during the National Oceanic and Atmospheric Administration California Nexus study in 2010. The contributions of emissions, chemical formation, and removal are quantified for each OVOC using CO as a tracer of emissions and the OH exposure of the sampled air masses calculated from hydrocarbon ratios. The method for separating emissions from chemical formation is evaluated using output for Pasadena from the Weather Research and Forecasting‐Chemistry model. The model is analyzed by the same method as the measurement data, and the emission ratios versus CO calculated from the model output agree for ketones with the inventory used in the model but overestimate aldehydes by 70%. In contrast with the measurements, nighttime formation of OVOCs is significant in the model and is attributed to overestimated precursor emissions and overestimated rate coefficients for the reactions of the precursors with ozone and NO3 . Most measured aldehydes correlated strongly with CO at night, suggesting a contribution from motor vehicle emissions. However, the emission ratios of most aldehydes versus CO are higher than those reported in motor vehicle emissions and the aldehyde sources remain unclear. Formation of several OVOCs is investigated in terms of the removal of specific precursors. Direct emissions of alcohols and aldehydes contribute significantly to OH reactivity throughout the day, and these emissions should be accurately represented in models describing ozone formation. Plain Language Summary: We report new measurements of volatile organic compounds (VOCs) in ambient air in the Los Angeles basin. Chemical reactions between VOCs and nitrogen oxides form ozone and fine particles, two important pollutants in Los Angeles smog. It is therefore important to understand VOC emission sources. In this work, we derive the composition of VOC emissions using ambient measurements at Pasadena in 2010. The study is complicated due to rapid chemical reactions that can form and remove VOCs in between the time of emission and measurement. After correcting for this chemistry, it is shown that emissions of many oxygen‐containing VOCs are important for the formation of ozone. Key Points: An extensive and expanded data set of oxygenated VOCs in ambient air in the Los Angeles basin is analyzed The composition of directly emitted oxygenated VOCs is determined after accounting for the effects of their chemical formation and removal Aldehydes are important for urban photochemistry, but their sources remain poorly understood